2007
DOI: 10.1529/biophysj.106.091017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Alignment within β-Sheets in Aβ14-23 Fibrils: Solid-State NMR Experiments and Theoretical Predictions

Abstract: We report investigations of the molecular structure of amyloid fibrils formed by residues 14-23 of the b-amyloid peptide associated with Alzheimer's disease (Ab 14-23), using solid-state nuclear magnetic resonance (NMR) techniques in conjunction with electron microscopy and atomic force microscopy. The NMR measurements, which include two-dimensional proton-mediated 13 C-13 C exchange and two-dimensional relayed proton-mediated 13 C-13 C exchange spectra, show that Ab 14-23 fibrils contain antiparallel b-sheets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
57
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 81 publications
(154 reference statements)
7
57
0
Order By: Relevance
“…Figure 4C shows the 2D 13 C NMR spectrum of morphologically homogeneous AMY05 fibrils in the dry, lyophilized state. Crosspeaks in Figure 4C are broader than in Figure 4B, as observed in previous solid state NMR studies of other amyloid fibrils when comparing lyophilized and hydrated states of the same sample (18,19,22,77,78). Line-narrowing in the hydrated state is attributed to increased molecular motions, which partially average out the inhomogeneous broadening of NMR chemical shifts that is present in all noncrystalline solids.…”
Section: Characterization Of Secondary Structure By 13 C Nmrsupporting
confidence: 74%
See 1 more Smart Citation
“…Figure 4C shows the 2D 13 C NMR spectrum of morphologically homogeneous AMY05 fibrils in the dry, lyophilized state. Crosspeaks in Figure 4C are broader than in Figure 4B, as observed in previous solid state NMR studies of other amyloid fibrils when comparing lyophilized and hydrated states of the same sample (18,19,22,77,78). Line-narrowing in the hydrated state is attributed to increased molecular motions, which partially average out the inhomogeneous broadening of NMR chemical shifts that is present in all noncrystalline solids.…”
Section: Characterization Of Secondary Structure By 13 C Nmrsupporting
confidence: 74%
“…In light of current knowledge that the ability to form amyloid fibrils is not an unusual property for a peptide (10), the fact that short peptides representing residues 20-29 form fibrils (56,89) does not imply that this segment constitutes the core of full-length amylin fibrils. In fact, the molecular structures of fibrils formed by short peptides can be qualitatively different from the structures of the corresponding segments in the context of full-length peptide fibrils, as demonstrated by findings that certain β-amyloid fragments form antiparallel β-sheets in amyloid fibrils (16,19,24,78), while other fragments (15,26,27) and full-length β-amyloid (15,17,21) form parallel β-sheets. Evidence from Griffiths et al for antiparallel β-sheets in fibrils formed by residues 20-29 of human amylin (25) indicates that, as in the case of β-amyloid fibrils, the molecular structures in fibrils formed by amylin fragments need not reflect the molecular structure of full-length amylin fibrils.…”
mentioning
confidence: 99%
“…20,64 The N/CHHC data presented here indicate that the polyglutamine fibrils investigated consist mainly of antiparallel β-sheets, in line with structural studies on shorter peptides that were also observed to adopt an antiparallel organization. [68][69][70][71][72] These findings may be a direct consequence of electrostatic interactions that favor an antiparallel arrangement of the charged peptide termini.…”
Section: Discussionmentioning
confidence: 99%
“…Electron spin resonance studies showed in-register parallel ␤-sheet structures of amylin (26), ␣-synuclein (Parkinson's disease) (27), and Tau (Alzheimer's disease and other 'tauopathies') (28). Some fragments of pathogenic peptides and crystal structures of peptides capable of forming amyloid filaments are found to have antiparallel or parallel structures (29)(30)(31)(32)(33), and recently the D23N mutant of A␤ has been found to adopt an antiparallel structure (34). In contrast, the Podospora prion [Het-s] is based on amyloid of the HET-s protein with a ␤-helical structure (35,36).…”
mentioning
confidence: 99%